Preferensi Konsumen Sayuran Organik di Plaza Asia Kota Tasikmalaya - Luthfy, Septihadi Muhammad; Nuraini, Candra; Bunda, Cici Aulia Permata; Isyanto, Agus Yuniawan (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The purpose of this study is to identify the attributes that are consumer preferences when purchasing organic vegetables using Conjoint Analysis and to analyze consumer attitudes towards purchasing organic vegetables using the Multiattribute Fishbein Analysis. The research was conducted from December 2023 to June 2024 at Plaza Asia, Tasikmalaya City. The Method Research used was a survey with 50 respondents selected using Incidental Sampling. The results of the Conjoint Analysis showed that Pearson's R was 0.915 with a significance of 0.001 and Kendall's Tau was 0.714 with a significance of 0.007, indicating a strong and significant relationship that supports the validity of the research on consumer purchase interest in organic vegetables. The analysis results showed that Freshness was the top priority attribute with an Importance Value of 47.874%, followed by Packaging at 18.793%, Organic Label at 17.840%, and Price at 15.493%. This indicates that consumers tend to prioritize Freshness over Price in their decision to purchase organic vegetables. Furthermore, the results of the Multiattribute Fishbein Analysis showed that consumers have a positive attitude towards organic vegetable products, with a total attitude score of 25.0164.